Background to the Constitution of 1823: between the Ancien Régime and the legal establishment of the Peruvian republican state - Tornero Cruzatt, Yuri (2023)
The aim of this article is to explain the background of the text of the Constitution of 1823 through the formation of the Republican State. The first section develops on the origins of the Peruvian State and the Peruvian republican law, briefly explaining the passage from the Spanish legal tradition to the republican law. The second section deals with the Protectorate of San Martín and the first institutional reforms, explains the swearing-in and the proclamation of independence, other related events, and also the first citizens’ rights, including the failure of the monarchical project. Finally, it explains the preparations for the adoption of the Constitution of 1823.